Analisis Resepsi Jurnalis Terkait Berita Pemidanaan Direktur JAKTV dengan Pasal Perintangan Penyidikan - Suryawati, Indah (Fakultas Ilmu Komunikasi UKWMS, 2025)
ABSTRACT In early 2025, news broke that JAKTV News Director Tian Bahtiar was implicated in a crude palm oil corruption case, sparking public and journalistic debate. This study describes and analyzes journalists’ responses to his indictment under obstruction of justice, using Stuart Hall's Encoding-Decoding Theory. The theory suggests that media messages are encoded by producers and interpreted differently by audiences. Through qualitative reception analysis, the study identifies three audience positions: dominant hegemonic, negotiated, and oppositional. Results show that journalists responded in varied ways—some aligned with the Attorney General's narrative, some negotiated it with ethical considerations, and others rejected it. These differences are shaped by factors like journalistic background, experience, and ethical integrity. The study highlights the dynamic relationship between media, law, and journalistic ethics, stressing the need to strengthen journalistic independence in the face of ethical challenges. ABSTRAK Awal 2025, muncul kabar Direktur Pemberitaan JAKTV, Tian Bahtiar, terseret kasus korupsi CPO dan dijerat pasal perintangan penyidikan oleh Kejaksaan Agung. Isu ini ramai diperbincangkan, termasuk di kalangan jurnalis, menunjukkan kuatnya pengaruh pesan media terhadap wacana publik. Penelitian ini bertujuan mendeskripsikan dan menganalisis resepsi jurnalis terhadap pemberitaan tersebut, menggunakan teori Encoding-Decoding Stuart Hall. Dengan metode reception analysis dan pendekatan kualitatif, ditemukan bahwa jurnalis merespons berita ini secara beragam: ada yang mengikuti narasi hukum, menegosiasikannya dengan etika jurnalistik, atau menolaknya. Perbedaan ini dipengaruhi latar belakang, pengalaman, posisi, dan integritas masing-masing. Hasil penelitian menegaskan bahwa hubungan media, hukum, dan etika jurnalistik bersifat dinamis, serta pentingnya menjaga independensi jurnalis di tengah berbagai tekanan.